2019
DOI: 10.1021/acs.energyfuels.9b02011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water/Decane Ratios and Salt on the Stability, Rheology, and Interfacial Tension of Water/Decane Emulsions

Abstract: This study investigates the effects of water/decane ratios and sodium chloride (NaCl) salt (1%−4%) on the water/decane emulsions with focus on the understanding of their stability, droplet sizes, rheology, and interfacial phenomena. Experimental results reveal that water/decane ratio has a great impact on the stability of water/decane emulsions. Reducing the water volume and increasing decane volume reduce the stability of water/decane emulsions. The instability is more pronounced at equal water/decane ratio. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…2,21,22 On the contrary, some studies have shown an increase in emulsion stability with salt. 19,30,51,82,83 To explain these discrepancies, we considered three factors: the surfactant/oil ratio (S/O) or the interfacial area, the length scales of observation, and the timescales of observation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,21,22 On the contrary, some studies have shown an increase in emulsion stability with salt. 19,30,51,82,83 To explain these discrepancies, we considered three factors: the surfactant/oil ratio (S/O) or the interfacial area, the length scales of observation, and the timescales of observation.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to explain our current observations that the addition of salt increased emulsion stability to coalescence, considering that this result is different from those of a majority of other emulsion stability studies. Many studies have shown that salt decreases the stability of oil-in-water emulsions stabilized by ionic surfactants, non-ionic surfactants, , proteins, and in the absence of added surfactants. , The addition of salt to an emulsion has even been suggested as a method to help flocculate, coalesce, and remove oil from wastewater systems. ,, On the contrary, some studies have shown an increase in emulsion stability with salt. ,,,, To explain these discrepancies, we considered three factors: the surfactant/oil ratio (S/O) or the interfacial area, the length scales of observation, and the timescales of observation.…”
Section: Discussionmentioning
confidence: 99%
“…The surface tension of 43− 53 mN/m obtained in this experiment is close to 52 mN/m as reported about the interfacial tension of the water/decane interface at 25 °C, which also indicates that our results are reasonable. 36 To be specific, after adding degassed water, the increase in surface tension from about 47 to 53 mN/m for droplet 3 implies an evident change of interfacial properties. The increase in surface tensions should be the reason for the increase in contact angles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The assembled structures can be tuned by varying the directions of the magnetic fields (Movie S1, Supporting Information), which has potential applications in sensor or display technology. To estimate the time scale of the assembly and the structural transition, we assume that colloidal particles of radius a = 4 µm are adsorbed at a decane-water interface, with a surface tension γ = 53.2 mN m −1 , and the effective viscosity μ = 0.91 mPa s. [25,26] Based on our simulation results, the estimated time scale of structural formation and transition is about t ≈ 1 ms, which is sufficiently fast to satisfy the requirements of responsive materials for advanced sensor or display technologies. For a possible experimental realization of our system, we note that magnetic spherical Janus particles have been experimentally fabricated [27][28][29][30] and investigated at a liquid-liquid interface.…”
Section: Doi: 101002/adma202006390mentioning
confidence: 99%